Antiviral Therapy Reduces Risk of Haemorrhagic Stroke in Patients with HCV Infection: A Nationwide Cohort Study. Issue 1 (January 2018) - Lin, Ming-Shyan; Chung, Chang-Min; Lin, Wey-Yil; Wei, Kuo-Liang; Wang, Jui; Lee, Ying-Ying; Hu, Jing-Hong; Tung, Tao-Hsin; Lin, Yu-Sheng
Background: The tendency for haemorrhagic stroke in patients with chronic HCV infection has emerged recently but the finding may be confounded by comorbidities. Proving the causality between HCV infection and haemorrhagic stroke is mandatory. Our study was designed to investigate the incidence of intracranial haemorrhage in HCV-infected patients with and without treatment. Methods: In the 11-year and population-based retrospective study, we acquired data from the Taiwan National Health Insurance Research Database. The patients with major comorbidities were excluded and 97, 198 HCV-infected patients were included for analysis. Treated and untreated cohorts were matched with propensity score to make the confounding factors in two groups comparable. Cox proportional hazard regression analysis was performed to evaluate the hazard ratio of haemorrhagic stroke in the cohorts. We applied survival analysis to compare the cumulative incidence of outcome events between the two cohorts. Results: After matching, the incidence density (ID) of haemorrhagic stroke in the untreated cohort is significantly higher than in the treated cohort (ID: 1.0 versus 0.6 events per 1, 000 person-years; P =0.0014). The adjusted hazard ratio (aHR) of haemorrhagic stroke is significantly reduced in the treated group ( P <0.05). Cumulative incidence of haemorrhagic stroke is significantly lower in the treated group than in the untreated group ( P =0.013). Conclusions: The study demonstrates that antiviral therapy significantly reduces the events of intracranial haemorrhage in HCV-infected patients and consolidates the novel concept that chronic HCV infection is a risk factor for haemorrhagic stroke.